A prospective, single-arm, open-label study to determine the safety and effectiveness of a fixed-dose combination of camylofin and mefenamic acid in Indian women with primary dysmenorrhea - Pandey, Pragya; Asava, Ayushi; Nagaraj, K. Hemalatha; Rath, Sudhanshu Kumar; Kodati, Vijaya Lakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Treatment of dysmenorrhea is aimed at providing symptomatic relief from associated pain. A prospective, single-arm, open-label, multicenter study was conducted at 5 sites across India to assess the safety, effectiveness and tolerability of a fixed-dose combination (FDC) of camylofin 50 mg and mefenamic acid 250 mg in women with primary dysmenorrhea. Methods: Women were prescribed a 3/5-day course of the FDC orally thrice daily. The primary endpoint was to assess the safety of the FDC as analyzed by incidence of adverse events (AEs), and the main secondary endpoint was to evaluate effectiveness by change in mean intensity of pain as assessed by visual analog scale (VAS) scoring from baseline to day 3/5. Results: Out of 274 enrolled women, pain associated with menses was reported by 271 (98.9%) women at baseline. In all, 28 (10.2%) women reported treatment-emergent AEs. The most common AEs were back pain, headache, vomiting, and upper abdominal pain, which were of mild intensity and resolved at the end of treatment (EoT). None of the women discontinued the study due to AEs. No serious AEs or deaths were reported in the study. The mean (standard deviation [SD]) pain intensity on VAS scale was 72.6 (16.28) at baseline and 3.3 (7.11) at EoT. A statistically significant reduction of 69.9 (18.60) from baseline in mean pain intensity was observed after treatment (p<0.0001). Conclusions: An FDC of camyolfin and mefenamic acid had a good safety and tolerability profile and could effectively relieve pain in Indian women with primary dysmenorrhea.